Dichloro-naphthoquinone as a non-classical inhibitor of the mycobacterial carbonic anhydrase Rv3588c12. Issue 6 (18th May 2017) - Dallaston, M. A.; Rajan, S.; Chekaiban, J.; Wibowo, M.; Cross, M.; Coster, M. J.; Davis, R. A.; Hofmann, A.
Abstract : This study reports the most active non-sulfonamide mycobacterial CA inhibitor to date. Abstract : The soluble mycobacterial carbonic anhydrases Rv3588c and Rv1284 belong to a different class of carbonic anhydrases than those found in humans, making them attractive drug targets by using the inherent differences in the folds of the different classes. By screening a natural product library, we identified naphthoquinone derivatives as a novel non-classical inhibitor scaffold of mycobacterial carbonic anhydrases that lack the sulfonamide/sulfamate group and thus did not affect human carbonic anhydrase II.